Expanding the framework of childhood adversity: Structural violence and aggression in childhood - Petrovic L.; Baker C.N.; Francois S.; Wallace M.; Overstreet S. (Child Protection and Practice)
Background: Structural violence harms youth by preventing them from meeting basic needs for safety, belonging, dignity, and agency, leading to negative outcomes like increased aggression. Such behaviors harm children's social and emotional well-being and academic success, particularly affecting Black youth who disproportionately experience structural violence. Although predictors of student aggression have been explored, the specific influence of structural violence—as measured through socioeconomic and racial disparities—remains under examined in the literature. This gap highlights the need for further investigation into how these external factors contribute to aggressive behaviors in school settings, Objective: This study sought to examine the relationship between structural violence and aggression, taking into account key student characteristics and features of the school climate. It was hypothesized that lower values of structural violence would predict increased student and teacher-reported aggression. Participants: and Setting: Participants included students and teachers across six New Orleans K-8 public charter schools. Methods: Structural violence was measured via the Index of the Concentration of the Extremes (ICE), a measure of economic and racial inequality within a geographic area. Student characteristics, neighborhood crime rate, and school climate variables were included as covariates. Results: Results showed that higher structural violence was significantly associated with student-reported aggression (β = −.12, p = .02) and with teacher-reported aggression (β = −.14, p = .02). Lower student-reported aggression was associated with higher perceptions of school safety (β = −.24, p = .04). Conclusions: Students from neighborhoods with greater structural violence exhibited higher levels of physical aggression, though lower reports of aggression are associated with better perceptions of school climate characteristics.